ANALISIS PROFITABILITAS USAHA KACANG GOYANG PADA INDUSTRI PRIMA RASA DI KOTA PALU - Max Nur Alam, Effendy, Pariyatna, (AGROTEKBIS, 2016)
The aim of this research is to know the income and the profitability business value in kacang goyang industry âPrima Rasaâ Palu City. This researchÂ conducted fromÂ April until May 2016. The determination of respondent was done intentionally (purposive). The number of respondent taken as many as 5 people. Analysis tools used wereÂ income analysis and profitability analysis. Analysis result of income indicatedÂ that the average income acquired from kacang goyang industryÂ of Â âPrima Rasaâ during two-monthÂ wasÂ Rp. 29.936.870. Analysis result of profitability showed that profitability value in February 9,82% it mean every Rp. 100 extra investment will gain Rp. 9,82 extra profit. Profitability value in MarchÂ was 13,44%Â it means thatÂ every Rp. 100 extra invesment will gain Rp. 13,44 extra profit. Analysis result of profitability showed that the invesment for execellent gain showedÂ thatÂ by profitability value increase from February to March 9,82% and 13,44%.Â